Dietary supplements in sport – side effects - Brożyna, Klaudia; Tkaczyk, Jędrzej; Rutkowska, Aleksandra (Journal of Education, Health and Sport, 2019)
Introduction: Dietary supplements (DS) were legalized for the first time in 1994 by the Dietary Supplements Health and Education Act. The statute defined DS as a source of one or more nutritional component such as minerals, herbs, vitamins, etc. Athletes are known as a distinctive group with the highest DS in sport intake (from 48-81%) The consumption of DS has been reported among recreational active individuals and non-athletesPurpose: present possible side effects caused by DS usage in sport.State of knowledge: Protein powders are common DS among athletes and bodybuilders, which consist of whey, casein, vegetable proteins in soy protein isolate (SPI). SPI contains week estrogens such as isoflavones genistein and daidzein. The surveys with isolated cases showed hepatic injury among athletes users of creatine, but the doses of DS were inappropriate and excessive. L-carnitine is a substance which is used due to its „fat-burning” abilities and a consequence of its higher intake are atherosclerotic lesions.Summary: DS in sport are used due to enhance muscle mass, duration, and efficiency of training. However, inappropriate usage of them may lead to many side effects. Athletes and professionals in sport should be consulted by the physician before and during the supplementation of DS in sport. Creatine is a substrate for a contraction of a muscle